2013
DOI: 10.1177/0363546513503444
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Meniscectomy After Meniscal Repair

Abstract: A meniscectomy after meniscal repair is performed infrequently, supporting the notion that repairing a meniscus is a safe and effective procedure in the long term. The risk for undergoing subsequent meniscectomies is decreased in patients undergoing a concomitant ACL reconstruction, in cases of isolated meniscal repairs for patients of older age, and in patients undergoing meniscal repair by surgeons with a high case volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 47 publications
6
79
2
4
Order By: Relevance
“…In addition, subsequent meniscectomy rates were dependent on surgeon volume and experience. 14 In that study, it is unclear whether subsequent meniscectomies involved the same area of the repair, and no outcomes data were available. In our study, all repairs were done by 1 surgeon, and the details regarding subsequent arthroscopies were documented.…”
Section: Steadman Et Almentioning
confidence: 97%
“…In addition, subsequent meniscectomy rates were dependent on surgeon volume and experience. 14 In that study, it is unclear whether subsequent meniscectomies involved the same area of the repair, and no outcomes data were available. In our study, all repairs were done by 1 surgeon, and the details regarding subsequent arthroscopies were documented.…”
Section: Steadman Et Almentioning
confidence: 97%
“…One treatment option for the injured meniscus is partial or total meniscectomy, although well-established data suggest that increased contact stresses occurring long term can lead to poor outcomes in many cases [2,3,11,[23][24][25]. Such findings have led to a renewed focus on meniscal preservation strategies to prevent articular cartilage degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies reported that healing rate in the age range of 20 -30 years was in its highest level (21,22), in the current study, there was no significant association between age and recovery rate according to IKDC and KOOS questionnaires. Although the prevalence of meniscal injury is higher in males than females, different studies showed no significant difference in the results of meniscal tear repair (8,23). In the current study, there was a significant association between gender and IKDC and symptom (S) scale scores.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%